INTERNATIONAL WAR: DECLINE, CONSEQUENCES, AND “PAX AMERICANA” - John Mueller (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2021)
The establishment and maintenance of any existing “world order” is primarily based on a general aversion to international war and does not depend on the United States. This perspective disputes two explanations that rely heavily on American activities. One contends that the United States, aided perhaps by the attention- arresting fear of nuclear weapons, was necessary to provide worldwide security and thus to order the world. The other contends that the United States was instrumental, indeed vital, in constructing international institutions, conventions, and norms, in advancing economic development, and in expanding democracy, and that these processes have crucially helped to establish and maintain a degree of international peace. This article traces the rise of an aversion to international war and argues that this, not US efforts, should be seen as the primary causative or facilitating independent variable in the decline of international war. This perspective also suggests that world order can survive, or work around, challenges that might be thrown at it by the United States or anyone else, that fears that a rising China or an assertive Russia will upset the order are overdrawn, that there is scarcely any need for the maintenance of a large military force in being, and that, under the right conditions, international anarchy, could well be a desirable state.